(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
The essay outlines the debate around the question on the existence of Medieval Aesthetics starting from the publication of Arte e bellezza nell’estetica medievale by Umberto Eco (1987). Since the last decade of the 20th century, the question on Medieval Aesthetics receives a particular attention from a methodological point of view also because it is close to different disciplines as History, History of Art, Aesthetics and History of Philosophy. A renewed interest in the image theme, in History and History of Art, permits to study the pre-modern period without using anachronistic categories like that of “Art”. In the field of Aesthetics scholars rethink how to approach the question about its history. In this context, History of Philosophy reviews its own categories asking how it is possible to talk about thematic objects that traditionally belong to Aesthetics.